1996
DOI: 10.1021/js950044j
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Description of the Effect of Molecular Size upon Electroosmotic Flux Enhancement during Iontophoresis for a Synthetic Membrane and Human Epidermal Membrane

Abstract: This study focused upon quantitatively determining the influence of permeant molecular size upon flux enhancement which results from electroosmosis. The first phase of the study involved validation of a fundamental model describing the molecular size dependence of flux enhancement which results from convective solvent flow. This was accomplished using a model synthetic membrane (stack of 50 Nuclepore membranes) and four model permeants with a molecular weight range of 60-504 (urea, mannitol, sucrose, and raffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 25 publications
3
49
0
Order By: Relevance
“…an increase in electroosmotic flux enhancement). Peck et al [42] studied the electroosmotic transport behavior across a synthetic membrane and skin and showed that flux enhancement due to electroosmosis was related to the molecular size of a permeant, which is consistent with the predictions from equation 9.…”
Section: Iontophoretic Transport Across the Polar Pathwaymentioning
confidence: 55%
See 2 more Smart Citations
“…an increase in electroosmotic flux enhancement). Peck et al [42] studied the electroosmotic transport behavior across a synthetic membrane and skin and showed that flux enhancement due to electroosmosis was related to the molecular size of a permeant, which is consistent with the predictions from equation 9.…”
Section: Iontophoretic Transport Across the Polar Pathwaymentioning
confidence: 55%
“…Thus, the extent of electroosmosis is related to the thickness of the double layer and the ionic strength of the solution in the pores of the skin. Through these relationships, skin electroosmosis has been used to characterize the skin polar pathway [41,42,43]. …”
Section: Iontophoretic Transport Across the Polar Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…For the iontophoretic transport of a neutral permeant, the Peclet number (Pe i ) is determined from the enhancement factor (E v,i ) by (Peck et al, 1996):…”
Section: Theory and Equationsmentioning
confidence: 99%
“…These phenomena support the hypothesis that the mechanism of enhancement by IP was mainly caused by the convective flow rate. 17,18) Thus chemicals that had increased convective flow with US treatment showed synergistic effects in skin penetration with USϩIP.…”
Section: Discussionmentioning
confidence: 99%